The effect of Literacy and Socio-economic status on issues related to adolescent girls - Gothi, Nilesh; Yadav, Gorav; Gothi, Aditi (International Journal of Contemporary Pediatrics, 2018)
Background: HIV/AIDS therefore is the most devastating disease and is getting worst instead of better. Girls and young women are highly vulnerable to HIV/AIDS and lack of education makes them more so. The aim of this study to assess the effect of Literacy and Socio-economic status on issues related to adolescent girl’s Reproductive and Sexual Health like menstrual hygiene, knowledge regarding reproduction, STD, AIDS in urban slums. Methods: This is a observational community based cross –sectional study carried -out on all the Adolescent girls married and unmarried from the age group above 13 to 19 years residing in the defined area. House to house survey of the eligible subjects was done by the researcher herself using a pre-designed and pretested schedule. Results: Out of total 376 respondents, majority 310 (82.44%) of adolescent girls knew about HIV/AIDS. most of the girls (69.67%) considered ‘Sharing contaminated needles’ as common mode of HIV/AIDS transmission out of which 86.57% were from above primary and 13.42% were from up to primary educational group. Most of the girls (69.67%) knew ‘Sharing contaminated needles as common mode of HIV/AIDS transmission. Our study shows that, most of the respondents (72.69%) wanted to know more about methods of prevention, out of which 63.45%, 29.44% and 7.10% girls were from lower, middle and higher SEC respectively. Conclusions: Adolescent girls undergo physical, emotional and psychological changes. Many doubts and questions arise in their minds especially regarding reproductive and sexual health leading to worries and anxieties. The various levels where interventions can be applied to improve adolescent girl’s reproductive and sexual health.